Effect of health promotion programs and home visits on chronic diseases - Baoum, Shada Omar; Binladin, Salman Ali; Althobaiti, Mohammed Fahad; Almousa, Mohammed Mousa; Awaji, Taghreed Mahdi; Alsulami, Faisal Turki; Al Shehri, Mona Omar; Asiri, Saud Yahya; Alhuthali, Mariam Mesfer; Alwahaimed, Abdulaziz Ahmed; Alharbi, Mohammed Awadh (International Journal Of Community Medicine And Public Health, 2021)
Evidence shows that the management of chronic disorders is associated with massive expenditure and increased utilization of healthcare resources. Therefore, innovative management approaches to these conditions are encouraged to overcome these burdens and enhance the quality of care for the affected patients. Home visits and health promotion programs have been described in this context with favorable outcomes over individuals and communities. We have discussed the efficacy of home visits and health promotion programs on the outcomes of patients suffering from chronic disorders. Our findings indicated the validity of these approaches in enhancing the quality of care for patients with chronic conditions. Adequately applying these outcomes can be associated with enhanced quality of life for patients. Besides, estimates also showed that they can reduce the number of visits to the emergency department and the frequency of hospital admissions. Health promotion programs can also reduce the utilization of the different healthcare resources including medication use and the availability of healthcare providers. However, the current evidence lacks validation by proper investigations. Accordingly, we encourage further studies to be conducted to enhance the current findings adequately.